Selenium intake is associated with gait speed in very old adults - Rocha, Camila Dias Nascimento; Henriques, Gilberto Simeone; Vasconcelos, Karine Aglio; Machado, Lucca Ferreira; Bicalho, Maria Aparecida Camargos; Santos, Rodrigo Ribeiro dos; Jansen, Ann Kristine (Frontiers in Aging, 2025)
IntroductionSelenium seems to have protective effect on muscle function, contribute to healthy aging and longevity, however, in older adults this relationship has not been well studied. Objective: To evaluate the nutritional status of selenium in very old adults and its relationship with muscle strength, muscle mass and physical performance.MethodsA cross-sectional observational study investigating functionally independent individuals aged ≥80 years was conducted. Appendicular skeletal mass was determined by electrical bioimpedance, and physical performance and hand-grip strength were evaluated. Selenium intake and status in plasma and erythrocytes were evaluated. For statistical analysis. Poisson multivariate analysis was performed, and prevalence ratio used as a measure of effect.ResultsA total of 72 older adults with a median age of 84 years were evaluated. Median Selenium intake was 71.58 mcg, and adequacy 73.5% overall, with a higher rate among men. In the total sample, 87.5% had optimal selenium plasma concentrations and no participants were deficient. All participants had adequate erythrocyte selenium levels. Gait speed was associated and correlated with selenium intake, even in the adjusted model The prevalence of low adequacy on the gait test was reduced by 3%–5% for every 1 mg increase in selenium consumption (PR 0.95; 95% CI: 0.93, 0.98).ConclusionThe gait speed results reinforce the hypothesis of an antioxidant role of selenium in muscle function. The very old adults studied demonstrated that homeostatic mechanisms control circulating selenium levels, highlighting the need for a specific reference value for the oldest-old population, besides the importance of analyzing blood markers associated with food intake and dietary patterns, since supplementation may prove iatrogenic.